1990
DOI: 10.1002/bbpc.19900940117
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Voltammetry for Electron Transfer Reactions at Liquid/Liquid Interfaces

Abstract: A theory for cyclic voltammetry at liquid/liquid interfaces for electron transfer is proposed, and the numerical solution of the resulting integral equation is evaluated. This theory has been used to show how the cyclic voltammograms, for electron transfer at ITIES, vary when different ratios of reactants and products, in both phases, are used, and how these voltammograms differ from classical cyclic voltammograms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 5 publications
2
17
0
Order By: Relevance
“…This behaviour is in agreement with the theoretical predictions made by Komorsky-Lovric´et al [30], which are based on the model analogous to that proposed by Girault et al [31]. In a previous work [30], considering the reaction (III), the authors have shown that the theoretical SW peak currents depend on one dimensionless parameter q, defined as the ratio between the initial concentration of the transferable anions in the water phase and the initial concentration of the redox probe in the organic phase, i.e.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This behaviour is in agreement with the theoretical predictions made by Komorsky-Lovric´et al [30], which are based on the model analogous to that proposed by Girault et al [31]. In a previous work [30], considering the reaction (III), the authors have shown that the theoretical SW peak currents depend on one dimensionless parameter q, defined as the ratio between the initial concentration of the transferable anions in the water phase and the initial concentration of the redox probe in the organic phase, i.e.…”
Section: Resultssupporting
confidence: 92%
“…Oppositely, when the concentration of glucose is equal or higher than the initial concentration of dmfc, the slope of the dependence E p vs. log[c(glucose) w ] is À54 mV. This behaviour is observed because the reaction (II) is of second order, and it is in complete agreement with the theoretical findings described in references [4,30,31].…”
Section: Resultssupporting
confidence: 87%
“…Electron transfer reactions at ITIES can be studied by cyclic voltammetry, but care has be taken when analysing the voltammetric response that depends strongly on the concentration ratio of the reactants. 12 A key issue when studying heterogeneous electron transfer reactions is to ensure that the reactants and the products do not partition to the adjacent phase. 9 Indeed, in the case of ferrocene, its partition to water cannot always be neglected and it has been shown that the reaction can take place on the aqueous side of interface.…”
Section: Electron Transfer Reactionmentioning
confidence: 99%
“…The current to an isolated particle formed at~=0 is given by Eq. (18). The current due to linear flux to the growing planar diffusion zone is given by (see Appendix A for derivation):…”
Section: Effect Of O6erlapping Diffusional Fieldsmentioning
confidence: 99%